A six-direction absolute displacement sensor for time-delayed control based on quasi-zero-stiffness property. (October 2016) - Jiao, Guyue; Sun, Xiuting
A novel six-direction sensor for absolute vibration motion is proposed in this study for the measurement of absolute motions by employing multi-direction quasi-zero-stiffness property. Scissor-like structures with pre-deformed springs are applied symmetrically in the proposed sensor. Based on the mathematical modeling of the proposed six-direction sensor, it is shown that the stiffness and damping properties of the sensor are adjustable nonlinear functions which are dependent on the structural parameters of scissor-like structures. And then, by utilizing bifurcation theory and perturbation method, the structural parameters are optimized for the improvement of measurement accuracy. For the realization of the approximate fixed point for a moving vibration object, the vibration from measurement object to the sensor is isolated, and thus the sensor could obtain the absolute motions. Utilizing the signals obtained by the proposed sensor directly, better vibration/suppression effectiveness is achieved. The results provide a novel and significant six-direction absolute motion measurement method by utilizing multi-direction quasi-zero-stiffness property with noticeable isolation performance only with passive elements.